2015
DOI: 10.1016/j.vetpar.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Systemic acute phase proteins response in calves experimentally infected with Eimeria zuernii

Abstract: Acute phase proteins (APPs) have been demonstrated to be useful in evaluating general health stress and diseases in cattle. Serum amyloid A (SAA) and haptoglobin (Hp) are APPs that are produced during inflammation, and likely play a role in host immunological defence against Eimeria infection and the associated intestinal tissue damage. We investigated the involvement of SAA and HP in an experimental study, including three groups of calves: a control group (group 0, n=11), and two groups infected with either 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…In D. viviparous experimental infection, the Hp concentration showed a peak 14 days after inoculation with L3 larvae, and although the animals had clinical signs of the infection (Gånheim et al, 2004), the Hp concentration was similar to our findings. These results were also similar to experimental infection with oocysts of Eimeria zuernii in calves, as Hp concentration peaked at 24 days after inoculation (Lassen et al, 2015), reaching similar Hp concentrations that were found in the group of GI parasites, demonstrating an inflammatory response caused by the effect of nematode and protozoan parasites in the small intestine mucosae.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In D. viviparous experimental infection, the Hp concentration showed a peak 14 days after inoculation with L3 larvae, and although the animals had clinical signs of the infection (Gånheim et al, 2004), the Hp concentration was similar to our findings. These results were also similar to experimental infection with oocysts of Eimeria zuernii in calves, as Hp concentration peaked at 24 days after inoculation (Lassen et al, 2015), reaching similar Hp concentrations that were found in the group of GI parasites, demonstrating an inflammatory response caused by the effect of nematode and protozoan parasites in the small intestine mucosae.…”
Section: Discussionsupporting
confidence: 83%
“…In the case of GI parasites, the cause of increases in Hp could be the damage caused to the GI tract, whereas in the lung parasites the increases in Hp could reflect subclinical chronic parasitic bronchitis and pneumonia caused by D. viviparous infection (Radostits et al, 2007). Increased Hp concentrations in calves were described in experimental D. viviparous and Eimeira zuernii infections (Gånheim et al, 2004;Lassen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Giardia infections can be chronic and last for months (Grit et al, 2014). Giardia and Eimeria have multifactorial pathogenesis that leads to microvilli alteration, diarrhoea, and weight loss in production animals (Olson et al, 1995;Geurden et al, 2010;Lassen et al, 2015). In a recent study, Giardia infection was also associated with haemorrhagic diarrhoea in calves (Lee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In response to APR, the concentrations of specific acute phase proteins (APP), serum amyloid A (SAA) and haptoglobin (HP), can increase in ruminant serum > 1000-fold (Ceciliani et al, 2012;Eklund et al, 2012). In cases of viral (foot-and-mouth disease and bovine respiratory syncytial virus) or parasitic (Eimeria and Cryptosporidium) infections, APP concentrations can increase in domestic ruminants' blood serum (Orro et al, 2011;Pourjafar et al, 2011;Stenfeldt et al, 2011;Lassen et al, 2015). In neonatal calves, APPs go through significant changes during first 2 to 3 weeks of life (Orro et al, 2008;Tóthová et al, 2015), suggesting that APPs have a role in the adaptation of neonate calves to the new environment.…”
Section: Introductionmentioning
confidence: 99%
“…A higher serum haptoglobin level was found in calves infected with Eimeria Zuernii than in the control, which may be in response to an increased demand for haptoglobin in the repair process as a result of haemolysis. An in ammatory stimulus will upregulate the hepatic synthesis of haptoglobin [44]. Induced myeloid leukemia cell differentiation protein Mcl-1 homolog, also known as Bcl2-L-3, is encoded by MCL1.…”
Section: Discussionmentioning
confidence: 99%